Capturing the Bigger Picture? Applying Text Analytics for Foster Open Innovation Processes for Sustainability-Oriented Innovation - Wehnert, Peter; Kollwitz, C.; Daiberl, Christofer; Dinter, Barbara; Beckmann, Markus (Sustainability, 2018)

Crowdfunding Sustainability-Oriented Innovations - Wehnert, Peter; Baccarella, Christian; Beckmann, Markus (R&D Management Conference, 2017)

In crowdfunding we trust? Investigating crowdfunding success as a signal for enhancing trust in sustainable product features - Wehnert, Peter; Baccarella, Christian; Beckmann, Markus (Technological Forecasting and Social Change, 2019)

Investigating Crowdfunding Success as a Signal for Enhancing Trust in Sustainable Product Features - Wehnert, Peter; Baccarella, Christian; Beckmann, Markus (Proceedings of the Academy of Management (AOM) Annual Meeting, 2018)

Investigating sustainable NGO–firm partnerships: An experimental study of consumer perception of Co-branded products - Heinl, Laura; Baatz, Anna; Beckmann, Markus; Wehnert, Peter (Sustainability, 2021)
With crises like climate change and degradation of the earth’s natural habitats, human consumption needs to become more sustainable to decrease humanity’s environmental footprint. Fostering sustainable consumer behavior by enabling consumers to make an informed choice for sustainable products is vital in changing human consumption for the better. To optimize consumers’ perception of sustainable products, companies can establish partnerships with environmental non-governmental organizations (NGOs). In practice, retailers and NGOs can engage in NGO–firm co-branding of sustainable products. Yet, little is known about the impact of this NGO–firm co-branding on consumer perception. We fill this gap based on a 2 × 2 × 2 experimental study. We test consumers’ trust, product and brand perception of co-branded sustainable products. Our study finds that NGO–firm co-branding has a significant positive effect on all the above. The effect is moderated by familiarity with the co-branding partnership and consumer attitudes. We discuss how those NGO– firm partnerships can be a useful tool to guide customers to more sustainable consumption choices. The results are discussed in light of sustainability communication and cross-sector partnership theory. We offer important insights for consumer perspectives on sustainability communication, business engagement of NGO–firm partnerships and develop future research ideas for consumer behaviour.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Co-branding; Sustainable cross-sector cooperation; Sustainable food sector

Online-Offline Co-Creation - Daiberl, Christofer; Danzinger, Frank; Dinter, Barbara; Hess, Joseph; Höckmayr, Benedikt; Jonas, Julia; Kollwitz, C.; Luzsa, Robert; Putz, Michael; Roth, Angela; Schmitt-Rüth, Stephanie; Wehnert, Peter (2016)

Partizipation durch Open Innovation: Wie kann Beteiligung die Nachhaltigkeit von eMobilität erhöhen? - Wehnert, Peter; Beckmann, Markus (Handbuch Energiewende und Partizipation, 2018)

Partizipative Entwicklung nachhaltigkeits-orientierter Innovationen - Wehnert, Peter; Beckmann, Markus (E-Mobilität gemeinsam gestalten. Erkenntnisse zur offenen und nutzerintegrierenden Dienstleistungsentwicklung aus dem Verbundprojekt CODIFeY, 2016)

Sustainable smart product-service systems: a causal logic framework for impact design - Ries, Lena; Beckmann, Markus; Wehnert, Peter (Journal of Business Economics, 2023)
Digital technologies can elevate product-service systems (PSS) to smart PSS, which focus on performance rather than ownership and are considered a means for dematerialization. However, transitioning to smart PSS does not guarantee sustainability. To understand the impact of smart PSS holistically, we take a two-pronged approach. First, we use the theory of change to conceptualize the causal link between sustainable smart PSS and their ultimate impact. We develop a three-step causal logic framework consisting of design, causation, and impact. Within this framework, we identify the business model properties of sustainable smart PSS as design characteristics and categorize the eventual impacts based on the triple bottom line. We introduce the term multi-causal pathway to describe the causation processes underlining the possibility of non-linearity and multi-causality. Second, we conduct a systematic literature review to investigate the mechanisms linking design and impact. Based on an analysis of 63 publications, we identify 17 specific mechanisms and group them into four types: information, resource, empowerment, and adverse mechanisms. Visualizing our results, we develop a morphological box as a toolkit for managers to develop their own impact-oriented logic model by identifying and activating the multi-causal pathway that fosters the desired sustainability effects. Moreover, discussing our framework, we develop research propositions and managerial questions for impact design. By linking the theory of change with the business model impact, we contribute toward a conceptual synthesis for understanding the impact of (sustainable) smart PSS.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Business model; Logic model; Morphological box; Product-service system; Smart technology; Sustainability; Theory of change

Sustainable smart product-service systems: a causal logic framework for impact design - Ries, Lena; Beckmann, Markus; Wehnert, Peter (Journal of Business Economics, 2023)